Inkubasi Produk Kuliner Kota Solok Sebagai Kota Transit dalam Upaya Meningkatkan Pendapatan UMKM yang Berdampak pada Peningkatan Pendapatan Asli Daerah - Silmi; Duma Putri Tama; Eka Candra Lina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
This community service aims to increase the income of Micro, Small, and Medium Enterprises (MSMEs) in Solok City through coaching 10 superior MSMEs under the auspices of the Solok City Tourism Office. The primary focus of this activity is on regional culinary products, namely Sobalari (Solok Bareh Lamak Onigiri) and Sopirang (Solok Pinyaram Pisang), which were developed by the Solok Belibis Creative (Sobiskraf) culinary team. Previously, they marketed the Sobalari and Sopirang products without calculating the even Point (BEP) and Margin of Safety (MOS), so MSMEs had difficulty determining the level of profit or loss. By socializing the concept of BEP and MOS calculations, this activity provided training and assistance to MSME players from the Sobiskraf culinary team. The results of practicing the BEP and MOS calculations show that there have been significant changes in determining the selling price of Sobalari and Sopirang products, which has positively impacted increasing MSME turnover. Implementing this more measurable financial strategy improves the welfare of MSMEs and contributes to increasing Solok City's Original Regional Income (ORI).